Pengaruh Mutu Pelayanan terhadap Kepuasan Pelanggan pada Suru-Suru All Delivery Panyabungan Kabupaten Mandailing Natal - Muhammad Fauzan; Ade Khadijatul Z Hrp; Muhlisah Lubis (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to determine the influence of service quality on customer satisfaction at Suru-Suru All Delivery Panyabungan, Mandailing Natal Regency. The type of research is quantitative research. Data collection techniques are by observation and distributing questionnaires. This research involved a sample of 86 respondents using the Slovin formula. All tests were carried out using the SPSS version 25 program. The results of this research were that service quality had a partial effect on customer satisfaction at Suru-Suru All Delivery Panyabungan, Mandailing Natal Regency. The partial test value (t) on the service quality variable (X) was 3.769 with a value ttable is 1.663. So the tcount value is greater than ttable (3.768 > 1.663), then the service quality variable (X) has a positive and significant impact on customer satisfaction (Y). This shows that the first hypothesis (Ha) is accepted. This means that